2013
DOI: 10.1007/s11033-013-2676-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of the nuclear factor kappa B inhibitor pyrrolidine dithiocarbamate in bladder ischemia–reperfusion injury in rats

Abstract: The aim of the present study was to evaluate the protective effects of the NF-кB inhibition with pyrrolidine-dithiocarbamate (PDTC) in ischemia-reperfusion (I/R) injury in the rat bladder. Twenty-four Sprague-Dawley male rats were divided into three groups. Group I; (n = 8) control, group II; (n = 8) I/R group; group III (n = 8) I/R and PDTC treatment. Superoxide dismutase (SOD), catalase (CAT), and gluatathione-S-transferase (GST) enzymes was studied in bladder tissue. Lipid peroxidation (as TBARS) levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Indeed, this protective effect of PDTC on GSH levels has also been reported in others models in rats, such as lipopolysaccharide‐induced hepatic injury, cisplatin‐induced testicular damage, ischaemia/reperfusion injury, and caecal ligation and puncture‐induced sepsis in rats . Moreover, supporting our results, PDTC restored the catalase activity in lipopolysaccharide‐induced oxidative stress, and in bladder ischaemia–reperfusion injury in rats …”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Indeed, this protective effect of PDTC on GSH levels has also been reported in others models in rats, such as lipopolysaccharide‐induced hepatic injury, cisplatin‐induced testicular damage, ischaemia/reperfusion injury, and caecal ligation and puncture‐induced sepsis in rats . Moreover, supporting our results, PDTC restored the catalase activity in lipopolysaccharide‐induced oxidative stress, and in bladder ischaemia–reperfusion injury in rats …”
Section: Discussionsupporting
confidence: 82%
“…PDTC is a low‐molecular‐weight thiol compound with great therapeutic potential as an anti‐inflammatory and antioxidant . PDTC was initially regarded as a potent inhibitor of NF‐κB, and it has been studied as a strong antioxidant compound to counteract the toxic effects of ROS .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrrolidine dithiocarbamate (PDTC) is a synthetic compound, which is largely used as antioxidant or nuclear factor kappa B (NF-B) inhibitor (Morais et al, 2010;Wiesener et al, 2011;Yucel et al, 2013). Previous studies have shown that PDTC could inhibit the replication of coxsackievirus B3 (CVB3), rhinovirus, influenza virus, and herpes simplex virus (Krenn et al, 2005;Qiu et al, 2013;Si et al, 2005;Uchide and Ohyama, 2003;Uchide et al, 2002;Wiesener et al, 2011), while the precise mechanism involved in the antiviral activity of PDTC has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…To study the effect of PDTC on NTT‐MMP‐2 expression in our IRI model, we randomly divided mice into four groups ( N = 6/group), PDTC‐treated control, PDTC‐treated IRI, vehicle‐treated control, and vehicle‐treated IRI. Mice in the treatment group received a 100 μl intra‐peritoneal (IP) injection of PDTC (Sigma–Aldrich, Inc., St. Louis, MO) at 30 mg/ml 1 h prior to ischemic injury as previously described . Mice in the vehicle groups received an equivalent dose of saline before injury.…”
Section: Methodsmentioning
confidence: 99%